ANALISIS PENGARUH EQUITY SENSITIVITY DAN ETHICAL SENSITIVITY TERHADAP PERILAKU ETIS AUDITOR - Kusuma, Ruth Novita Dani; Budisantoso, Antonius Totok (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
AbstractÂ This study aims to identify and analyze the effect of equity sensitivity and ethical sensitivity to the ethical behavior of auditors in the public accounting firm in Surabaya in 2016. The sample used in this study were fifty eight respondents, which were auditors in the city of Surabaya, where the data was collected through questionnaires distributed. The analysis is based on respondents' answers were obtained through a questionnaire with random method (random) were distributed in the city of Surabaya. Results of the research showed that equity sensitivity positive effect on ethical behavior and ethical sensitivity auditor positive influence on the ethical behavior of auditors.Â Keywords: equity sensitivity, ethical sensitivity, and ethical behavior of auditors